Pengaruh Game “Sakura School Simulator” Terhadap Perkembangan Sosial Anak Usia Dini - Muhammad Raihan Nafis Suwarna; Idat Muqodas; Finita Dewi (Departement of Mathematics Education, 2023)
The digital era is a time when information is more easily gained using the intermediary of digital technology. In this digital era there is something called online games. The purpose of this research is to find out whether the game